1999
DOI: 10.1089/thy.1999.9.871
|View full text |Cite
|
Sign up to set email alerts
|

Special Features of Graves' Disease in Early Childhood

Abstract: Graves' disease (GD) is extremely rare in children younger than 4 years of age, but if not recognized and treated it can seriously interfere with growth and development. We report three unrelated children, all females, in whom GD occurred before the age of 3. These children presented with goiter, exophthalmos, tachycardia, and hyperactivity. Moreover, one showed a severe psychomotor delay, and had previously undergone surgery due to craniosynostosis; the other two manifested a language delay. All had high thyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
13

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(63 citation statements)
references
References 29 publications
3
47
0
13
Order By: Relevance
“…By contrast, thyrotoxicosis in children accelerates growth and skeletal maturation but also causes short stature due to early fusion of the growth plates. Premature fusion of the sutures of the skull is also seen in severely affected young children and may lead to craniosynostosis (5). These observations demonstrate sensitivity of the skeleton to disturbances of thyroid status during postnatal growth and indicate the importance of thyroid hormones during bone development.…”
mentioning
confidence: 75%
“…By contrast, thyrotoxicosis in children accelerates growth and skeletal maturation but also causes short stature due to early fusion of the growth plates. Premature fusion of the sutures of the skull is also seen in severely affected young children and may lead to craniosynostosis (5). These observations demonstrate sensitivity of the skeleton to disturbances of thyroid status during postnatal growth and indicate the importance of thyroid hormones during bone development.…”
mentioning
confidence: 75%
“…Palpebral retraction is related with thyrotoxicosis and exophthalmos is related with autoimmune pathology. The clinical picture resolves in 3-16 weeks with elimination of maternal antibodies (15). It has been reported that biochemical hypothyrodism is observed in both twins initially, whereas hyperthyroidism may be observed in one and biochemical hypothyroidism may be observed in the other subsequently (28).…”
Section: Clinical Picturementioning
confidence: 96%
“…The growth problem is related with both hyperthyroidism and preeclampsia. Other fetal findings include tachycardia (heart beat >160/min), heart failure, hydropsis, acceleration in bone age, craniosynocstosis, and microcephaly (15).…”
Section: Treatment Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…A tireotoxicose juvenil pode estar associada ao crescimento acelerado e à idade óssea avançada. No entanto, há relatos de redução da estatura devido à fusão prematura das placas de crescimento (Segni et al, 1999;Bassett et al, 2007).…”
Section: Introductionunclassified